Doc management: Proposal for a doctoral management system - Isidoro, R.; Alturas, B.; Ramalho, N. (HCI International 2022 Posters. Communications in Computer and Information Science, 2022)
Control is an essential function for good management, for which a bureaucratic organization, that is, a system of rules, regularized procedures, division of responsibilities, and hierarchy, contributes. This paper addresses the issues related to a problem encountered in the management of doctorate students. Traditionally manual, this process is no longer efficient. This brings problems such as difficulty in searching a student’s file and its information, difficulty in noticing if a student is undocumented, or in figuring out what tasks must be completed and turned in and what dates to do so. The current system is prone to delays, errors and requires unnecessary effort. The goal of this work was to develop a proposal to solve the problems described, by means of an application, with a simple interface, that can manage, create and edit students, their information, their grades and their deliveries, manage, create and edit curricular units and the related information, manage create and edit academic teachers and their functions. In other words, it is intended that the application is able to facilitate the management of all course processes and document a student's academic path. This will provide workers with a better quality of life, reducing the probability of error and generating gains in quality and efficiency in the management of student processes, thus improving the professional life of those who use the application.